2009
DOI: 10.1371/journal.pone.0005014
|View full text |Cite
|
Sign up to set email alerts
|

Reserves Protect against Deforestation Fires in the Amazon

Abstract: BackgroundReserves are the principal means to conserve forests and biodiversity, but the question of whether reserves work is still debated. In the Amazon, fires are closely linked to deforestation, and thus can be used as a proxy for reserve effectiveness in protecting forest cover. We ask whether reserves in the Brazilian Amazon provide effective protection against deforestation and consequently fires, whether that protection is because of their location or their legal status, and whether some reserve types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
2
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 53 publications
4
108
2
7
Order By: Relevance
“…mongabay.com/2008/0926-amazon.html). More generally, major forest fires are less frequent near roads in Amazonian PAs (including semi-protected reserves and indigenous lands) than near roads in unprotected forest (Figure 4) [86].…”
Section: Reducing Forest Invasionsmentioning
confidence: 99%
“…mongabay.com/2008/0926-amazon.html). More generally, major forest fires are less frequent near roads in Amazonian PAs (including semi-protected reserves and indigenous lands) than near roads in unprotected forest (Figure 4) [86].…”
Section: Reducing Forest Invasionsmentioning
confidence: 99%
“…Third Way as Paradigm of Sustainable Development for the Amazon In terms of development policy pathways for the Amazon, two modes have historically dominated: (i) a valuable nature conservation approach with large swathes of territory legally protected from any economic and human activity outside indigenous peopleswhich comprise 2.1 million km 2 , or about 43% of Brazilian Amazon (153,163,164); and (ii) an approach that has focused on conversion or degradation of forests for the production of either protein commodities (e.g., meat and soya) or tropical timber at the forest frontier and the build-out of massive hydropower generation capacity-which together have been historically responsible for massive deforestation of the Amazon (30,31) and generated other significant negative externalities.…”
Section: Impacts Of Anthropogenic Drivers Of Change In the Amazonmentioning
confidence: 99%
“…Adeney, Christensen, and Pimm (2009) observed that 90% of satellite active fire detections derived from a variety of polar orbiting satellites occurred within 10 km of official roads in the Brazilian Amazon. Similarly, 50% and 95% of MODIS active fire detections were found to occur within 1 and 10 km, respectively, of official and unofficial roads and navigable rivers in the BTMFB (Kumar et al 2014).…”
Section: Distance To Roads and Navigable Riversmentioning
confidence: 99%